Batasan Tanggung Jawab Hukum Notaris dalam Pembuatan Akta Berdasarkan Peraturan Perundang-Undangan - Bintang, Amar; Fachrul Aljamili, Muhammad; Griptoni, Gio; Lasmini, Lasmini; Mustia Ningsih, Wida (Adagium: Jurnal Ilmiah Hukum, 2025)
The study was intended to analyze the limitations of notary legal responsibilities in deed creation based on regulatory regulations in Indonesia. The notary has the authority to make an authentic deed that has high proof power before the law, but its legal responsibilities are set within clear boundaries. Such restrictions include the obligation to observe the regulations of legislation, to ensure the legitimacy of information on the part of the party, to keep confidentiality, and to refuse papers that violate social or legal norms. Additionally, the role of the notary is also very important in ensuring that deeds made meet the legal requirements, do not harm either side, and are done with due diligence and transparency. The study used a regulatory approach with a normative-analysis method to explore the regulations governing the notary professions and the legal responsibilities attached to them.